Problem-Based Learning (PBL) Methods Within An Independent Curriculum(A Literature Review) - Alifatun Ni’mah; Eka Syovi Arianti; Suyanto Suyanto; Shidqi Hamdi Pratama Putera; Ahmad Nashrudin (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
In this article, the author provides an overview of the implementation of problem-based learning (PBL) methods within an independent curriculum. The introduction section introduces the topic and highlights the significance of PBL in education, while the overview of PBL methods section explains the key principles and components of this pedagogical approach. The importance of an independent curriculum is discussed in terms of empowering students to develop critical thinking, problem-solving, and self-directed learning skills. The article then outlines the benefits of implementing PBL, including enhanced critical thinking skills, improved problem-solving abilities, and increased engagement and motivation. Finally, the challenges and considerations of implementing PBL are addressed, such as the need for adequate teacher training and support, the development of new assessment strategies, and the integration of PBL with existing curricula. The article concludes by offering best practices for successful implementation, such as establishing clear learning objectives and outcomes and fostering a collaborative learning environment.